1992
DOI: 10.1007/bf00132273
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in sympatric populations of diploid and polyploid brine shrimp (Artemia parthenogenetica)

Abstract: We examined genetic variation in sympatric diploid and polyploid brine shrimp Artemia parthenogenetica from each of three populations (China, Italy and Spain). Italian and Spanish tetraploids are closely related (I = 0.964). Diploids and tetraploids within each of the two European populations are also closely related (mean I = 0.905). Most alleles found in diploids also exist in sympatric polyploids. In contrast, the asexual Artemia (2N, 4N and 5N) in our study share few alleles with their close sexual relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 15 publications
(13 reference statements)
0
12
0
Order By: Relevance
“…It has been described in some asexual invertebrate families and a few vertebrate hybrids [26,68–71] and is mostly associated with allopolyploidy. Autopolyploidy is much less common and is usually not associated with parthenogenesis, perhaps with the exception of some high arctic ostracods and polyploid populations of the brine shrimp Artemia parthenogenetica [72,73]. Artificially induced autopolyploid shrimp and fish are usually sterile [74], making the combination of autopolyploidy and parthenogenesis in marbled crayfish rather unique.…”
Section: Discussionmentioning
confidence: 99%
“…It has been described in some asexual invertebrate families and a few vertebrate hybrids [26,68–71] and is mostly associated with allopolyploidy. Autopolyploidy is much less common and is usually not associated with parthenogenesis, perhaps with the exception of some high arctic ostracods and polyploid populations of the brine shrimp Artemia parthenogenetica [72,73]. Artificially induced autopolyploid shrimp and fish are usually sterile [74], making the combination of autopolyploidy and parthenogenesis in marbled crayfish rather unique.…”
Section: Discussionmentioning
confidence: 99%
“…This supposition was not supported strongly by data documented to date. Some studies have evidenced triploid and tetraploid parthenogenetic Artemia had lower genetic variation than diploids (Zhang & King ; Maniatsi et al . ), but the pentaploids from Dongfanghong Saltern (China) had higher genetic variability in comparison with its sympatric diploid and other allopatric diploids and tetraploids (Zhang & King ).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have evidenced triploid and tetraploid parthenogenetic Artemia had lower genetic variation than diploids (Zhang & King ; Maniatsi et al . ), but the pentaploids from Dongfanghong Saltern (China) had higher genetic variability in comparison with its sympatric diploid and other allopatric diploids and tetraploids (Zhang & King ). Zhang & King () proposed that the genetic differences among allopatric di‐ and polyploidy populations could be attributed to the interaction among environmental parameters, ploidy levels and origins, while the dissimilarities between sympatric diploids and polyploids could result from the influence of ecological isolation.…”
Section: Introductionmentioning
confidence: 99%
“…There is no second polar body and the product of the first division divides endomitotically, generating nuclei with 2n = 42 chromosomes. The tetraploids probably arose automitotically [Zhang et al, 1991] via a process like this. As shown in figure 2 , this mode of meiosis produces homozygous offspring from a heterozygous female in a single generation.…”
Section: Gamete Duplicationmentioning
confidence: 99%
“…Figure 2 shows the process of meiotic division as it occurs in a diploid animal such as the phyllopod crustacean Artemia parthenogenetica . The genus Artemia comprises 8 species that are often collectively called A. salina in the literature and which have diploid (2n = 42), triploid, tetraploid, pentaploid, octoploid, and decaploid races [Gross, 1932;Browne et al, 1984;Zhang et al, 1991]. Artom [1931] showed that the first meiotic division in diploid females at a population in Sète, southern France, proceeds in the normal fashion, eliminating 21 chromosomes.…”
Section: Gamete Duplicationmentioning
confidence: 99%